Response surface optimization of kraft lignin recovery from pulping wastewater through emulsion liquid membrane process - Ooi, Zing Yi (Taylor and Francis Inc., 2016)
Kraft lignin (KL) represents a key sustainable source of biomass for transformation into biofuels and high-value specialty chemicals. Excess lignin in pulping wastewater creates pollution problems, hence affecting human. Thus, the KL recovery from pulping wastewater by emulsion liquid membrane was investigated and optimized using response surface methodology in this study. The liquid membrane was prepared by dissolving carrier tricaprylylmethylammonium chloride (Aliquat 336) and hydrophobic surfactant sorbitan monooleate (Span 80) in kerosene (diluent) with sodium bicarbonate (NaHCO3) as the internal stripping phase and 2-ethyl-1-hexanol as the modifier. The comparison between the experimentally optimized, and the RSM optimized values was accomplished by optimizing the following parameters: carrier and stripping agent concentration and treat ratio of emulsion to feed phase. The maximum KL recovery of 97% was obtained under the optimum condition at 0.012 M of Aliquat 336, 0.32 M of NaHCO3, and 1:4.8 of treat ratio.